(NkOLEBATELXNYE I WRA]ATELXNYE SPEKTRY MNOGOATOMNYH MOLEKUL (B:s ((NwWEDENIE W TEORI@(B) /s - (Nt@LIN(B, (NwLADIMIR iWANOWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 192 (17 (NNAZW(B.) 203 (30 (NNAZW(B.)s
Keywords: (NmOLEKULY MNOGOATOMNYEs; (NsPEKTROSKOPIQ MOLEKULQRNAQs